Auditory processing and neuropsychological profiles of children with functional hearing loss. (November 2018) - Rashid, SK Mamun Ur; Mukherjee, Dipankar; Ahmmed, Ansar Uddin
Abstract: Objectives: This paper compares structured history, auditory processing abilities and neuropsychological findings of children with functional hearing loss (FHL) to those with suspected auditory processing disorder without FHL (control). The main aim was to evaluate the value of a holistic assessment protocol for FHL used in a routine pediatric audiology clinic. The protocol incorporated a commercially available test battery for auditory processing disorder (APD), non-verbal intelligence (NVIQ) and tools to screen for common co-existing neurodevelopmental conditions such as attention deficit hyperactivity disorder (ADHD), language impairment (LI) and developmental coordination disorder (DCD). The outcome of such holistic assessment was expected to help in understanding the nature of FHL and to provide individualized support to mitigate their difficulties. Methods: This retrospective study compared two groups, 40 children (M = 17, F = 23) in each group between seven and sixteen years of age, one group with a history of FHL and the other with suspected APD without FHL (control). The groups were matched against age, gender, hand use, diagnosis of APD or non-APD (31 with APD and 9 without APD in each group) and non-verbal intelligence. All the children were healthy English speaking children attending mainstream schools with no middle or inner ear abnormalities. Structured history was obtained from parents regarding different nonacademic and academic concerns. The SCAN-3:C and SCAN-3:A test batteries were used to assess auditory processing abilities; Lucid Ability test for NVIQ; Children's Communication Checklist-2 (CCC-2) for language ability; Swanson Nolan and Pelham-IV Rating Scale (SNAP-IV) for ADHD; and the manual dexterity components of the Movement Assessment Battery for Children-2 (MABC-2) as a screening tool for DCD. Results: About 60% of children in both the groups had concerns regarding listening in noisy background. In the history, poor attention was reported in 45% of children in the FHL group compared to 82.5% in the control group (p < 0.01). Hyperacusis was present in 35% of children in the FHL group and in 62% of children in the control group (p < 0.05). Concerns about overall academic abilities were present in 59% of children in the FHL group and 75% of the controls (p > 0.05). Only 15% of children in the FHL group had concerns with numeracy skills in contrast to 41% of the controls (p < 0.05). Significantly fewer (p < 0.01) children in the FHL group (41%) received additional support at school than the controls (75%). Fewer children performed poorly in Filtered Words (FW) test of the SCAN-3 batteries, 30% in the FHL group and 17.5% in the control group, in contrast to Auditory Figure Ground 0 (AFG0), 85% in FHL and 80% in the control group. The number of children performing poorly in AFG0 was significantly higher compared to all the other SCAN-3 tests in FHL (P < 0.05), in contrast to FW and Competing Sentences (CS) only in the control group (p < 0.05). The control group had higher prevalence of atypical ear advantage (AEA) in left directed Competing Words (CW) (32.5%) and Time Compressed Sentences (TCS) (32.5%) compared to FW (7.5%). In contrast, FHL group had higher prevalence of AEA in AFG0 (48.7%) compared to CS (21%). High proportions of children in both the groups had LI (80% in FHL and 82.5% in the control group), with significantly lower (p < 0.05) levels of ADHD symptoms in the FHL group (39.5%) compared to the control group (72.5%). Impaired manual dexterity was present in 30.7% of children in FHL group and 47.5% in the controls. Conclusions: The prevalences of APD and language impairment are high compared to ADHD symptoms in children with FHL, and holistic assessment is recommended. Despite some similarities in the auditory and neuropsychological profiles between children with FHL and those with suspected APD without FHL some differences were noted. The results suggest that children with FHL have genuine difficulties that need to be identified and addressed. Future research is required to identify the neural pathways which could explain the similarities and dissimilarities between the two groups.